3D Resin-coated pressure sensor response for bite force assessment: A pilot study - Tânia Soares; Marco Marques; Cláudia Barbosa; Mário Vaz; Maria Helena Figueiral (Tabriz University of Medical Sciences, 2023)
Background. Occlusal splints with sensors help in the bruxism diagnosis and monitoring, by recording the patient's bite force. The aim of this study was to evaluate the accuracy of a pressure sensor when it is covered with different thicknesses of a 3D printing resin (Anycubic 405nm Translucent Green UV Resin, Anycubic, UK). Methods. In this preliminary study, the evaluated sensor (FlexiForce A201 Sensor, Tekscan) was firstly calibrated without any type of cover material, and later tested with 3D printing resin with different thicknesses (1 mm, 1.15 mm, 1.4 mm and 1.6 mm). The load tests were performed by a force tester (MultiTest 2.5 dV, Mecmesin). Results. When the pressure sensor was covered with resin of 1mm and 1.6 mm thick specimens, a higher difference was found between the applied load and the corresponding sensor reading. Conclusion. It was concluded that it is possible to use this type of pressure sensor and that it showed better accuracy with the 1.15 mm and 1.4 mm 3D printing resin covering.